The Effect of The Think Pair Share Method on Improving Reading Skills German Language for Class 11 High School Students - Manalu, Marilin Devi Hani Mitra; Hutagalung, Insenalia Sampe Roly; Purba, Lydia (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This research aims to determine the effect of the Think Pair Share (TPS) method on improving German reading skills at the A2 level among twelfth-grade students of SMA Negeri 4 Pematangsiantar. This study employed a quantitative approach with a Pre-Experimental method and a One Group Pretest-Posttest Design. The research instrument consisted of a cloze test and essay questions. The sample of this study was class XII-2 with a total of 35 students. Based on the descriptive analysis, the average pretest score was 48.83 and the average posttest score was 86.2. The results of hypothesis testing using the paired sample t-test showed that the tcount value was 26.023, while the ttable value at the significance level of 0.05 with df = 34 was 2.032. Since tcount > ttable (26,023 > 2,032), H1 is accepted and H0 is rejected. Furthermore, the N-Gain score was 73%, which is categorized as high. Thus, it can be concluded that the Think Pair Share method has a significant effect on improving German reading skills at the A2 level among twelfth-grade students of SMA Negeri 4 Pematangsiantar